LINK-A: unveiling its functional role and clinical significance in human tumors - Liao, Bing; Wang, Jialing; Xie, Yilin; Luo, Hongliang; Min, Jun (Frontiers in Cell and Developmental Biology, 2024)
LINK-A, also recognized as LINC01139, has emerged as a key oncological lncRNA in cancer. LINK-A is upregulated in solid and liquid tumor samples, including breast cancer, ovarian cancer, glioma, non-small-cell lung cancer, and mantle cell lymphoma. Notably, LINK-A is involved in regulating critical cancer-related pathways, such as AKT and HIF1α signaling, and is implicated in a range of oncogenic activities, including cell proliferation, apoptosis, epithelial-mesenchymal transition (EMT), cell invasion and migration, and glycolysis reprogramming. LINK-A’s differential expression and its correlation with clinical features enable it to be a promising biomarker for cancer diagnosis, prognosis, and the stratification of tumor progression. Additionally, LINK-A’s contribution to the development of resistance to cancer therapies, including AKT inhibitors and immunotherapy, underscores its potential as a therapeutic target. This review provides a comprehensive overview of the available data on LINK-A, focusing on its molecular regulatory pathways and clinical significance. By exploring the multifaceted nature of LINK-A in cancer, the review aims to offer a valuable resource for future research directions, potentially guiding the development of novel therapeutic strategies targeting this lncRNA in cancer treatment.